Design and application research on management information system security architecture in digital campus - Xin-zheng LONG; Cheng-jie XING; Rong-bin OUYANG; Qian-yi WANG; Li LI; Yun-feng LIU (Tongxin xuebao)
Aiming at the university management information system security threats and challenges,a security architecture named 1C4GS was proposed.First connotation and function of five important components of 1C4GS was expounded,which named security management center,security communication network,security region boundary,security computing environment and security application.Then we used “basic personal data reporting system” as an example to construct the management information system security arrangement application based on 1C4AS,this arrangement application integrated a variety of security technologies and strategies such as transparent data encryption,user Identify,form edit cache as a whole to,and achieved the management information system’s network security,border security,computing environment security and application security.